When β‐cells fail: lessons from dedifferentiation. (September 2016) - Accili, D.; Talchai, S. C.; Kim‐Muller, J. Y.; Cinti, F.; Ishida, E.; Ordelheide, A. M.; Kuo, T.; Fan, J.; Son, J.
Abstract : Diabetes is caused by a combination of impaired responsiveness to insulin and reduced production of insulin by the pancreas. Until recently, the decline of insulin production had been ascribed to β‐cell death. But recent research has shown that β‐cells do not die in diabetes, but undergo a silencing process, termed "dedifferentiation." The main implication of this discovery is that β‐cells can be revived by appropriate treatments. We have shown that mitochondrial abnormalities are a key step in the progression of β‐cell dysfunction towards dedifferentiation. In normal β‐cells, mitochondria generate energy required to sustain insulin production and its finely timed release in response to the body's nutritional status. A normal β‐cell can adapt its mitochondrial fuel source based on substrate availability, a concept known as "metabolic flexibility." This capability is the first casualty in the progress of β‐cell failure. β‐Cells lose the ability to select the right fuel for mitochondrial energy production. Mitochondria become overloaded, and accumulate by‐products derived from incomplete fuel utilization. Energy production stalls, and insulin production drops, setting the stage for dedifferentiation. The ultimate goal of these investigations is to explore novel treatment paradigms that will benefit people with diabetes.